Evaluasi Penerimaan dan Kesuksesan Implementasi Integrated Billing System (IBS) menggunakan Technology Acceptance Model dan Human Organization Technology - Fit Model pada PT. PELINDO III Cabang Tanjung Wangi - Pujo Prasetyo Aji; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Integrated Billing System (IBS) is an information system which developed by PT. PELINDO to facilitate the exchange of data and information of a harbor. This system is based on website applications which integrated between agencies and industrial player. However, in the process of application to each branch appear a different success rate due to various factors that exist in each branch. The objective of this research is to describe the acceptance and success rate of the implementation IBS using the Technology Acceptance Model (TAM) and the Human Organization Technology (HOT-Fit) model. Data collection was done by spreading the questionnaire where the number of respondents selected was 18 respondents based on saturated sample technique. The results of this study indicate that the acceptance level of the IBS system has reached good category with the value reaching 79.35%. While the success rate based on HOT-Fit model reached 79.56% and categorized good.